2022
DOI: 10.1108/ohi-03-2022-0081
|View full text |Cite
|
Sign up to set email alerts
|

Student housing design implications for single-room occupancy during COVID-19 in Ghana

Abstract: PurposeThe adaptation of emerging building designs for single room occupancy in off-campus university student housing during the COVID-19 pandemic is evolving. However, assessing its effects on student satisfaction to compensate for COVID-19-associated impacts is missing. As a result, the study examines the satisfaction of students with emerging building designs in single-room off-campus student housing in Ghana.Design/methodology/approachThe study is quantitatively based on positivist philosophical thinking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
(168 reference statements)
1
4
0
Order By: Relevance
“…The study further showed that thermal comfort had a high and negative impact on the health of SWD in Ghanaian student housing as supported by Appau et al . (2022).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The study further showed that thermal comfort had a high and negative impact on the health of SWD in Ghanaian student housing as supported by Appau et al . (2022).…”
Section: Discussionsupporting
confidence: 58%
“…The study further showed that thermal comfort had a high and negative impact on the health of SWD in Ghanaian student housing as supported by Appau et al (2022). Reliance on artificial ventilation (fans and air conditioners) was revealed as the most crucial variable that reduces sweat and suffocation on SWD, in line with Simpeh and Shakantu (2019).…”
Section: Pm 424mentioning
confidence: 66%
See 2 more Smart Citations
“…Consequently, in Ghana, more than 75% of student housing provision is handled by the private sector (Attakora-Amaniampong et al , 2021), and more than 80% of these students stay in off-campus housing facilities (Ameyaw et al , 2016). Designs of these buildings are usually focused on interior facilities satisfaction with less focus on exterior security (Appau et al , 2022). However, violent crime (such as rape cases and student riots) and property crime (such as stealing and break-in) within student housing are significant concerns for university authorities in Ghana (Kwame Nkrumah University of Science and Technology, 2023; University of Ghana, 2023; Adzimah et al , 2020).…”
Section: Introductionmentioning
confidence: 99%